PENGARUH PAJAK ATAS KATEGORI LAPANGAN USAHA REAL ESTAT DAN PAJAK ATAS KATEGORI LAPANGAN USAHA PERDAGANGAN BESAR DAN ECERAN; REPARASI DAN PERAWATAN MOBIL DAN SEPEDA MOTOR TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BADUNG SELATAN - Martami Sari, Ida Ayu Gede Dika (Jurnal Mahasiswa Perpajakan, 2014)
Real Estate Sector Category and Tax on Wholesale and Retail Trade Business Sector Category; Car and Motorcycle Repair and Maintenance on Tax Revenue on Pratama Tax Office South Badung has the potential to provide a huge tax contributions on tax revenues at Pratama Tax Office South Badung. The purpose of the research to determine the significance of the tax effects of the two categories of the business sector to tax revenues on Pratama Tax Office South Badung. The design of the research is an explanatory quantitative approach. The results of this study indicate that: First, there is influence collectively (simultaneous) both independentÂ  variable that is tax on Real Estate Sector Category and Tax on Wholesale and Retail Trade Business Sector Category: Car and Motorcycle Repair and Maintenance. Second,there is a significant influence on each independent variable on the dependent variable which is receiving tax. Third,independent variable tax on real estate business category has a strong influence on tax revenue compared to the other independent variables. Keywords: Real Estate, Wholesale, Retail, Repair, Maintenance, Car, Motorcycle and tax revenue